Altered regulation of Akt signaling with murine cerebral malaria, effects on long-term neuro-cognitive function, restoration with lithium treatment. - Minxian Dai (Public Library of Science (PLoS), 2012)
Neurological and cognitive impairment persist in more than 20% of cerebral malaria (CM) patients long after successful anti-parasitic treatment. We recently reported that long term memory and motor coordination deficits are also present in our experimental cerebral malaria model (ECM). We also documented, in a murine model, a lack of obvious pathology or inflammation after parasite elimination, suggesting that the long-term negative neurological outcomes result from potentially reversible biochemical and physiological changes in brains of ECM mice, subsequent to acute ischemic and inflammatory processes. Here, we demonstrate for the first time that acute ECM results in significantly reduced activation of protein kinase B (PKB or Akt) leading to decreased Akt phosphorylation and inhibition of the glycogen kinase synthase (GSK3β) in the brains of mice infected with Plasmodium berghei ANKA (PbA) compared to uninfected controls and to mice infected with the non-neurotrophic P. berghei NK65 (PbN). Though Akt activation improved to control levels after chloroquine treatment in PbA-infected mice, the addition of lithium chloride, a compound which inhibits GSK3β activity and stimulates Akt activation, induced a modest, but significant activation of Akt in the brains of infected mice when compared to uninfected controls treated with chloroquine with and without lithium. In addition, lithium significantly reversed the long-term spatial and visual memory impairment as well as the motor coordination deficits which persisted after successful anti-parasitic treatment. GSK3β inhibition was significantly increased after chloroquine treatment, both in lithium and non-lithium treated PbA-infected mice. These data indicate that acute ECM is associated with abnormalities in cell survival pathways that result in neuronal damage. Regulation of Akt/GSK3β with lithium reduces neuronal degeneration and may have neuroprotective effects in ECM. Aberrant regulation of Akt/GSK3β signaling likely underlies long-term neurological sequelae observed in ECM and may yield adjunctive therapeutic targets for the management of CM.